Uric acid elevation in pediatric patients with dilated cardiomyopathy and prediction of mortality - Han, Yong; Chen, Cheng; Qin, Suyuan; Liu, Dongli; Pang, Yusheng (Frontiers in Cardiovascular Medicine, 2024)
Background and aims Pediatric dilated cardiomyopathy (DCM) is a primary cause of heart failure, highlighting the urgent need for effective prognostic markers. Methods We performed a single-center retrospective study involving 145 children diagnosed with DCM, with a median follow-up period of 4.0 months (interquartile range: 6.2–108.4 months). The relationship between serum uric acid (SUA) levels and all-cause mortality was assessed using Kaplan–Meier survival curves, multivariate Cox proportional hazard models, and restricted cubic spline (RCS) models. Results Of the 145 children with DCM (median age 5.7 years; 61.4% male), 45 (31%) died within 1 year, and 65 (44.8%) died during the maximum follow-up period. In adjusted multivariate Cox regression models, each log2 SUA increase was linked to a higher risk of 1-year mortality [hazard ratio (HR), 2.66; 95% confidence interval (CI), 1.41–5.01] and overall mortality (HR, 1.97; 95% CI, 1.15–3.37). The highest SUA tertile showed a greater risk of mortality at 1 year (HR, 4.26; 95% CI: 1.5–12.06) and during the maximum follow-up (HR, 2.56; 95% CI: 1.06–6.16) compared with the lowest tertile. RCS models indicated an inverted L-shaped association between baseline SUA levels and overall mortality risk, with age-stratified analyses revealing a linear and U-shaped relationship in children ≤10 and >10 years, respectively. Further age-stratified analyses highlighted the modifying effect of age on this association. Conclusion Elevated SUA levels are a significant predictor of mortality in pediatric DCM, with a pronounced impact on children under 10 years of age. Therefore, SUA levels could serve as potential biomarkers for risk stratification in this population.